Growth and inflation: Estimation of threshold point for Nepal - Bhusal, Tara Prasad; Silpakar, Sajana (Economic Journal of Development Issues, 2012)
This article is primarily meant to estimate threshold level of inflation in Nepal using annual data for the period 1975-2010. The threshold value of inflation is found to be 6% for Nepal. Beyond that level of inflation rate, higher or lower than the threshold value, the economic growth can be jeopardized. Looking specifically at Nepal’s economic and inflation performance, the less than robust link between the two variables is not surprising, given the current structure of the economy and factors which influence inflation.DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7216 Economic Journal of Development Issues Vol.13 & 14 2011, pp.131-138